Carnal Hermeneutics - Treanor, Brian; Kearney, Richard (Book collections on Project MUSE., 2015)
Building on a hermeneutic tradition in which accounts of carnal embodiment are overlooked, misunderstood, or underdeveloped, this work initiates a new field of study and concern. Carnal Hermeneutics provides a philosophical approach to the body as interpretation. Transcending the traditional dualism of rational understanding and embodied sensibility, the volume argues that our most carnal sensations are already interpretations. Because interpretation truly goes "all the way down," carnal hermeneutics rejects the opposition of language to sensibility, word to flesh, text to body. In this volume, an impressive array of today's preeminent philosophers seek to interpret the surplus of meaning that arises from our carnal embodiment, its role in our experience and understanding, and its engagement with the wider world.